Keloid Intralesional Excision Reduces Recurrence: A Meta-analytic Study of the Available Literature on 608 Keloids - Nathan G. Lawera, MD; Jules Madzia, PhD; Liann C. Casey, MD; Rodney L. Guyton, MD; Kiersten C. Woodyard De Brito, BS; Alexandra Kinzer, MD; Raquel M. Ulma, MD, DDS; Brian S. Pan, MD; Ann R. Schwentker, MD; Angelo A. Leto Barone, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. The objective of this meta-analysis was to examine the effectiveness of keloid intralesional excision (KILE) in preventing recurrence. Treatment of keloids using surgical excision alone leads to high rates of recurrence. To date, there are no widely accepted guidelines for keloid treatment, and a multitude of adjunctive therapies are used to reduce recurrence. Despite these efforts, recurrence remains high. In this study, we conducted a meta-analysis of the existing literature on KILE to determine its role in recurrence reduction. Methods:. A literature review using PubMed, Scopus, and Web of Science databases was performed. Two authors independently evaluated studies for eligibility. Incidence of keloid recurrence was recorded, and a comprehensive meta-analysis was performed to assess the pooled keloid recurrence rate, as well as the effect of additional therapies. Results:. Twenty-two studies evaluating intralesional excision of 608 keloids were included in the study. Average time to follow-up was 19.2 months (range 6–35 months). A meta-analysis of proportions was conducted, demonstrating a pooled recurrence rate of 13% (95% confidence interval, 9%–16%). There was no evidence that using therapies in addition to KILE had a significant effect on the overall pooled recurrence rate. Conclusions:. A meta-analysis of 608 keloids shows that KILE is an effective technique in preventing keloid recurrence, with a pooled recurrence rate of 13% compared with previously reported rates of 45%–100% after complete excision. Although there are no standard guidelines for keloid treatment, our meta-analysis shows that KILE is promising in recurrence reduction.